Production of Malaysian soil erodibility nomograph in relation to soil erosion issues - 436508 Tew, Kia Hui (Skudai : Universiti Teknologi Malaysia, 1996)
Thesis (Master of Civil Engineering (Hydrology)) - Universiti Teknologi Malaysia, 1996